Estimasi Jumlah Murid Baru Menggunakan Metode Forecasting - Dwi Harini; Lilia Sinta Wahyuniar (Journal of Instructional Mathematics, 2021)
Of the many forecasting methods or forecasting, the Linear Regression Method can be used to predict or predict the number of new students or students in the new academic year at the Islamic Junior High School "Al-H****h in Malang Regency. This study uses the MAD, MSE, and MAPE approaches. The data used is historical data on the number of students obtained for 9 years starting from the 2013-2014 school year until the 2021-2022 school year. By estimating or forecasting, helping the school, especially the AL-H****h Islamic Junior High School, know the number of new students accepted at the school in the 2022-2023 school year.